Financial Derivatives in Banking and Finance: A Bibliometric Overview of Research Trends - Rahmiyati, Nekky; Kaswoto, Junet; Sungkowati, Sri (The Es Accounting And Finance, 2025)
This study provides a bibliometric analysis of the research trends in financial derivatives within the banking and finance literature. By examining citation patterns, co-authorship networks, and keyword co-occurrences, the study identifies key research themes and their evolution over time. The analysis reveals the central role of derivatives in risk management and financial stability, particularly in the wake of financial crises. It highlights the growth of computational techniques in derivatives pricing and risk management, with an increasing focus on advanced models and simulations. The study also explores the emerging influence of blockchain technology and decentralized finance in reshaping the derivatives landscape. The bibliometric map underscores the global nature of financial derivatives research, with significant contributions from the United States, China, and the United Kingdom. The study provides valuable insights for scholars, practitioners, and policymakers, suggesting areas for further research, particularly in regulatory frameworks, pricing models, and the integration of new technologies in the derivatives market.